Global Status of Toxoplasma gondii Seroprevalence in Rodents: A Systematic Review and Meta-Analysis - Galeh, Tahereh Mikaeili; Sarvi, Shahabeddin; Montazeri, Mahbobeh; Moosazadeh, Mahmood; Nakhaei, Maryam; Shariatzadeh, Seyyed Ali; Daryani, Ahmad (Frontiers in Veterinary Science, 2020)
Toxoplasmosis is one of the most prevalent infections in humans and animals caused by the intracellular protozoan parasite Toxoplasma gondii (T. gondii). Rodents, as intermediate and reservoir hosts, play a key role in the maintenance and transmission of T. gondii. They can be contaminated and maintain the parasite in the form of cysts in their bodies, demonstrating an infection source for their offsprings, predators (particularly felids), and other animals. Therefore, the present systematic review and meta-analysis study was carried out to evaluate the global seroprevalence of T. gondii in these mammals. For achieving the purpose of the current study, six English databases (PubMed, Science Direct, Web of Science, Scopus, ProQuest, and Google Scholar) were systematically searched for related studies from 1970 to 2018. Finally, a total of 52,372 records were screened, 105 records including 26,221 rodents were incorporated in the present study. By random effect models, the overall seroprevalence was calculated at 6% (95% CI=6–7%), with the highest amount was observed in Africa (24%) and South America (18%), and the lowest amount in Europe (1%). The subgroup data analysis by gender manifested that the prevalence of Immunoglobulin G antibodies did not differ between genders (P>0.05). Due to the significant heterogeneity, meta-regression models were applied based on serological techniques and continental regions; however, the obtained values were not statistically significant (P=0.480 and P=0.295, respectively). The present study revealed a relatively low level of T. gondii seroprevalence in rodents; however, if they were the main food source for their predators, they would cause high transmission of T. gondii.